Effect of TCNQ Layer Cover on Oxidation Dynamics of Black Phosphorus - Meingast, Laura; Kolesnik-Gray, Maria; Siebert, Martin; Abellán, Gonzalo; Wild, Stefan; Lloret, Vicent; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas; Krstic, Vojislav (Physica Status Solidi-Rapid Research Letters, 2018)
Keywords: Dynamics; Oxidation; Black phosphorus; TCNQ

Effect of TCNQ Layer Cover on Oxidation Dynamics of Black Phosphorus - Meingast, Laura; Kolesnik-Gray, Maria; Siebert, Martin; Abellan Saez, Gonzalo; Wild, Stefan; Lloret Segura, Vicente Josep; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas; Krstic, Vojislav (Physica Status Solidi-Rapid Research Letters, 2018)
The puckered surface of black phosphorus represents an ideal substrate for an unconventional arrangement of physisorbed species and the resulting specific two-dimensional chemistry of this system. This opens the way to investigate the chemical and physical properties of locally confined areas of black phosphorus without the necessity for further physical downscaling of the material. We have evaporated tetracyanoquinodimethane (TCNQ) on top of black phosphorus under over-saturation non-equilibrium conditions in vacuum. The evolution of linear density and height of droplets formed through oxidation during exposure to air is studied time dependently by scanning-force microscopy. Our study suggests that the TCNQ molecules spontaneously arrange in a thin layer of the order of a few nm height, which, however, is fragmented with a periodicity of about 100nm. It is shown that within the confined space separating the layer fragments the chemical dynamics of the oxidation process is remarkably different than on a bare black phosphorus surface.
Keywords: black phosphorus; dynamics; oxidation; TCNQ

Fingerprints of magnetoinduced charge density waves in monolayer graphene beyond half filling - Hoffmann, Felix; Siebert, Martin; Duft, Antonia; Krstic, Vojislav (Scientific Reports, 2022)
A charge density wave is a condensate of fermions, whose charge density shows a long-range periodic modulation. Such charge density wave can be principally described as a macroscopic quantum state and is known to occur by various formation mechanisms. These are the lattice deforming Peierls transition, the directional, fermionic wave vector orientation prone Fermi surface nesting or the generic charge ordering, which in contrast is associated solely with the undirected effective Coulomb interaction between fermions. In two-dimensional Dirac/Weyl-like systems, the existence of charge density waves is only theoretically predicted within the ultralow energy regime at half filling. Taking graphene as host of two-dimensional fermions described by a Dirac/Weyl Hamiltonian, we tuned indirectly the effective mutual Coulomb interaction between fermions through adsorption of tetracyanoquinodimethane on top in the low coverage limit. We thereby achieved the development of a novel, low-dimensional dissipative charge density wave of Weyl-like fermions, even beyond half filling with additional magneto-induced localization and quantization. This charge density wave appears both, in the electron and the hole spectrum.
CRIS-Team Scopus Importer:2024-12-16

Monolayer black phosphorus by sequential wet-chemical surface oxidation - Wild, Stefan; Lloret, Vicent; Vega-Mayoral, Victor; Vella, Daniele; Nuin, Edurne; Siebert, Martin; Kolesnik-Gray, Maria; Loeffler, Mario; Mayrhofer, Karl J. J.; Gadermaier, Christoph; Krstic, Vojislav; Hauke, Frank; et al. (RSC Advances, 2019)
We report a straightforward chemical methodology for controlling the thickness of black phosphorus flakes down to the monolayer limit by layer-by-layer oxidation and thinning, using water as solubilizing agent. Moreover, the oxidation process can be stopped at will by two different passivation procedures, namely the non-covalent functionalization with perylene diimide chromophores, which prevents the photooxidation, or by using a protective ionic liquid layer. The obtained flakes preserve their electronic properties as demonstrated by fabricating a BP field-effect transistor (FET). This work paves the way for the preparation of BP devices with controlled thickness.
CRIS-Team WoS Importer:2019-02-21

Unconventional conductivity increase in multilayer black phosphorus - Kolesnik-Gray, Maria; Meingast, Laura; Siebert, Martin; Unbehaun, Tim; Huf, Tobias; Ellrott, Günter; Abellan Saez, Gonzalo; Wild, Stefan; Lloret Segura, Vicente Josep; Mundloch, Udo; Schwarz, Julian; Niebauer, Michael; et al. (npj 2D Materials and Applications, 2023)
Multilayers of so-called 2D van der Waals materials have gained considerable attention as active components of next-generation electronic and optoelectronic technologies, with semiconducting black phosphorus (BP) regarded as one of the most promising systems. The applicability and performance limits of BP in both stand-alone and heterostructure-based multilayer devices are determined by individual flake charge transport properties, which synergistically depend on the number of layers and the strength of interlayer coupling between those. In this work, we study the DC electrical transport characteristics of high-quality BP field-effect devices within a wide range of flake thicknesses at room temperature. The experimental data show a non-trivial increase in conductivity and hole density with a reduced number of layers while maintaining constant field-effect mobility due to the prevalence of electron–phonon scattering. Based on the solution of the 1D Schrödinger–Poisson equation, we find that the observed phenomena are a direct consequence of non-negligible interlayer coupling, which in turn causes a local redistribution of free charge carriers towards the central layers. Our data show that due to the electrostatic conditions at the flake surfaces, a naturally protected 2D hole gas can be encapsulated in flakes as high as 10 nm, which preserves the bulk-like bandgap and effective carrier masses due to the electrostatic environment.
CRIS-Team Scopus Importer:2023-04-14